New Challenges in Wood and Wood-Based Materials - Réh, Roman; Krišťák, Ľuboš; Kubovský, Ivan (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue of Polymers is a collection of 11 original high-quality scientific contributions on basic and applied research in the field of wood science and technology, and provides good examples of the recent challenges related to the production and application of wood and wood-based materials. The Special Issue includes individual papers concerned with the enhancement of the performance and technological properties of wood composites, above all plywood, as well as with the ignition and combustion of wood and wood composites in monitoring and evaluating these processes on state-of-the-art equipment, and monitoring chemical changes in wood and wood adhesives and composites. The topic of the Special Issue has clearly resonated with the world's scientific community and the responses have come from traditionally strong wood research centers in Europe and Asia.